Causal relationship between gut microbiota and gynecological tumor: a two-sample Mendelian randomization study - Xiong, Yajun; Zhang, Xiaonan; Niu, Xiaoya; Zhang, Long; Sheng, Yanbing; Xu, Aiguo (Frontiers in Microbiology, 2024)
Introduction Previous research has established associations between alterations in gut microbiota composition and various gynecologic tumors. However, establishing a causal relationship between gut microbiota and these tumors remains necessary. This study employs a two-sample Mendelian randomization (MR) approach to investigate causality, aiming to identify pathogenic bacterial communities potentially involved in gynecologic tumor development. Methods Data from the MiBioGen consortium’s Genome-Wide Association Study (GWAS) on gut microbiota were used as the exposure variable. Four common gynecologic neoplasms, including uterine fibroids (UF), endometrial cancer (EC), ovarian cancer (OC), and cervical cancer (CC), were selected as outcome variables. Single-nucleotide polymorphisms (SNPs) significantly associated with gut microbiota were chosen as instrumental variables (IVs). The inverse variance-weighted (IVW) method was used as the primary MR analysis to assess the causal relationship. External validation An was conducted using an independent. Sensitivity analyses were performed to ensure robustness. Reverse MR analysis was also conducted to assess potential reverse causation. Results Combining discovery and validation cohorts, we found that higher relative abundance of Lachnospiraceae is associated with lower UF risk (OR: 0.882, 95% CI: 0.793-0.982, P = 0.022). Conversely, higher OC incidence is associated with increased relative abundance of Lachnospiraceae (OR: 1.329, 95% CI: 1.019–1.732, P = 0.036). Sensitivity analyses confirmed these findings’ reliability. Reverse MR analysis showed no evidence of reverse causation between UF, OC, and Lachnospiraceae. Discussion This study establishes a causal relationship between Lachnospiraceae relative abundance and both UF and OC. These findings provide new insights into the potential role of gut microbiota in mechanisms underlying gynecological tumors development.